1994
DOI: 10.1155/s0962935194000177
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Leishmania (L.) amazonensis Growth inCultured Mouse Macrophages by Prostaglandins and Platelet Activating Factor

Abstract: Ttm role of endogenously synthesized PAF and prostaglandins on the infection of mouse macrophages by Letsbmanta (L) amazonensis was investigated, as well as the possible correlation between the effects of these inflammatory mediators with nitric oxide production. It was found that pretreatment of macrophages with 10-M of the PAF antagonists, BN-52021 or WEB-2086, increased macrophage infection by 17 and 59%, respectively. The cyclooxygenase inhibitor, indomethacin (10 g/ml), induced a significant inhibition wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 0 publications
6
23
1
Order By: Relevance
“…PGE 2 decreases macrophage leishmanicidal activity. In a previous study we showed that the addition of PGE 2 to resident macrophages obtained from susceptible BALB/c mice induced a significant increase in the infection index (25). Here we confirmed this effect of PGE 2 in TG-elicited macrophages of C57BL/6 mice.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…PGE 2 decreases macrophage leishmanicidal activity. In a previous study we showed that the addition of PGE 2 to resident macrophages obtained from susceptible BALB/c mice induced a significant increase in the infection index (25). Here we confirmed this effect of PGE 2 in TG-elicited macrophages of C57BL/6 mice.…”
Section: Resultssupporting
confidence: 87%
“…We have previously shown that the addition of PGE 2 to resident BALB/c macrophages strongly reduced their leishmanicidal capacity (25). In the present study we confirmed this observation in TG-elicited macrophages obtained from C57BL/6 mice.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although PAF enhanced killing of L. amazonensis, some of its antagonists inhibited the parasite clearance in mouse macrophages (13)(14)(15). Accordingly, PAF receptor (PAF receptor) is perhaps the most feasible candidate to serve as an HPC receptor.…”
mentioning
confidence: 99%